Analisis Sistem Pengendalian Internal Persediaan Barang Dagang Menggunakan The Committee Of Sponsoring Organization Of Treadway Commission (COSO) Pada Distributor Sparepart Kendaraan Bermotor Oriens Jaya Medan - Salsabilla Febriani; Muhammad Arif; Nurwani Nurwani (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to determine the internal control system for merchandise inventory in the company and the internal control system for merchandise inventory using COSO as well as the obstacles faced in the internal control system for merchandise inventory. This research uses a qualitative method with a descriptive approach, with data collection techniques through interviews, observation and documentation. The data sources for this research are primary data and secondary data. The research results obtained from this research are: firstly, the internal control system for merchandise inventory at the Oriens Jaya Medan Motor Vehicle Spare Parts Distributor is implemented based on established procedures, secondly, the internal control system for merchandise inventory uses COSO from 5 (five) components which have 17 ( seventeen) the principles contained in all of these principles have been answered but there are some that do not yet exist in the company including code of ethics and ethical standards, officially written organizational structure, does not have an audit committee, does not have CCTV, does not set strict sanctions , and there was no bar code scanning device, and the third problem faced was human error which resulted in inventory differences and delays in sending goods by expeditions, damage to goods due to expeditions and customers (shops) taking a long time to send returned goods.